The Modifikasi Tata Rias Pengantin Muslim Bekasri Lamongan: Modikasi Tata Rias Pengantin Muslim Bekasri Lamongan - Pramesi Nariswari, Lindy; Faidah, Mutimmatul; Maspiyah, Maspiyah; Pritasari, Octaverina Kecvara (Jurnal Tata Rias, 2026)
Abstrak This study aims to Modify Traditional Bekasri Lamongan Bridal Makeup into Muslim clothing that is in accordance with Islamic values, without eliminating local cultural identity. This research is based on the lack of response from the Lamongan community to Bekasri bridal makeup because it is not in accordance with Muslim clothing norms. This study uses a qualitative descriptive approach with stages of exploration, design, embodiment, and assessment. Data were obtained through interviews, observations, documentation, and assessment sheets by 30 respondents consisting of makeup experts, lecturers, and students. The results of the study showed that design 1 was chosen as the best design. The results of the embodiment changed without eliminating the characteristics of the Bekasri bride such as, make-up, clothing color, additional accessories worn. The conclusion of this study is that the modification of Bekasri Lamongan Muslim bridal makeup is acceptable and has the potential to be an alternative choice for the Muslim community without eliminating traditional cultural elements. Keywords: Modification of bridal makeup, Bekasri Bride, Research methods, embodiment